Artificial Sweeteners Induce Glucose Intolerance by Altering the Gut Microbiota. Issue 1 (January 2015) - Suez, Jotham; Korem, Tal; Zeevi, David; Zilberman-Schapira, Gili; Thaiss, Christoph A.; Maza, Ori; Israeli, David; Zmora, Niv; Gilad, Shlomit; Weinberger, Adina; Kuperman, Yael; Harmelin, Alon; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Noncaloric artificial sweeteners (NASs) are popular because of their low caloric intake and perceived health benefits for weight loss and normalization of blood sugar levels. Artificial sweeteners have been increasingly introduced as an additive into common foods as an alternative to high-caloric sugars. However, increased consumption has coincided with a dramatic increase worldwide in obesity and diabetes epidemics. Scientific data supporting the safety and benefits of NAS consumption are sparse and controversial. Most NASs are not digested in the gastrointestinal tract and directly encounter the intestinal microbiota. The diet modulates microbiota composition and function in the healthy/lean state as well as in obesity and diabetes mellitus. Intestinal dysbiosis has been associated with propensity to metabolic syndrome. The investigators studied NAS-mediated changes of microbiota composition and function of mice to determine whether chronic NAS consumption exacerbates glucose intolerance in mice. Formulations of saccharin, sucralose, or aspartame were added to the drinking water of mice. The data provide conclusive proof that NAS-mediated intestinal dysbiosis is directly responsible for the development of glucose intolerance in mice. Treating mice with antibiotics eradicated many intestinal bacteria and fully reversed artificial sweeteners' effects on glucose metabolism. Transfer of fecal microbiota from mice that consumed artificial sweeteners to "germ-free" mice resulted in a complete transmission of the glucose intolerance into the recipient mice. Incubating the microbiota anerobically with artificial sweeteners also induced glucose intolerance in the sterile mice. Profound changes in the population of intestinal bacteria have been linked to host susceptibility to obesity, diabetes, and other metabolic diseases in both mice and humans. Similar NAS-induced dysbiosis and glucose intolerance were demonstrated in healthy human subjects. These findings show that NAS consumption in both mice and humans increases the risk of glucose intolerance through adverse metabolic effects mediated by intestinal dysbiosis. The data suggest that the widespread use of NAS should be reassessed.